Intricacies of Religious Language in Shaping the Mindset of Adherents during COVID-19: A Study of Churches in Calabar - Duke, Emmanuel Orok (International bulletin of mission research, 2024)
Religious language has the potential to shape the mindsets of human beings. Further, it is probable that religious utterances will affect adherents’ responses to real-life situations. With the aid of speech-act theory, this article investigates how religious utterances used by church leaders in framing public discourse modified some social perceptions of Christians during the COVID-19 pandemic. The research shows the impacts and limitations of speech-act theory concerning the influence of church leaders over their adherents during the COVID-19 era. In dialogue with the CAN-CRS Report, the research shows that some Christians differed from their pastors on certain COVID-19 related issues.